The Use of Magoosh Application to Enhance EFL College Students’ Vocabularies at English Department - Indri Elsa Adrianti; Leni Marlina (Universitas Negeri Padang, 2022)
There are some ways to enhance students’ vocabularies. One of them is using online applications, Magoosh Application. This study is to determine the efficiency of utilizing the Magoosh application in enhancing the vocabularies of students in the English Department of UNP. An experimental research design will use in this study to investigate the extent to which the use of these applications. Also, the instrument of data collection technique are tests and a questionnaire. The respondents in this study were 20 students of English Department of Universitas Negeri Padang. They were given pre-test before using Magoosh and post-test after using Magoosh. Then, followed by giving 15 questions for questionnaire. The results showed that there is an improvement from the pre-test to the post-test after the students use Magoosh application. The improvement is 24.53%. The pre-test and post-test proved to be higher in the final test. It can be concluded that using the Magoosh application can improve students' vocabulary. Moreover, from the satisfaction of the students it shows that 63% of the respondents agree that Magoosh helps them to enhance their vocabularies. Thus, the implementation of Magoosh application is usually recommended to be an exciting technique in coaching gaining knowledge of method to inspire the students in vocabulary.